1995
DOI: 10.1093/ajcn/62.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Calcium requirements of lactating Gambian mothers: effects of a calcium supplement on breast-milk calcium concentration, maternal bone mineral content, and urinary calcium excretion

Abstract: The calcium requirement for prolonged lactation was investigated in a randomized supplementation study of Gambian mothers consuming a low-calcium diet (7.1 mmol/d, or 283 mg/d). Sixty women were studied from 10 d to 78 wk of lactation, receiving calcium or placebo for the first 12 mo. The supplement increased average calcium intake by 17.9 mmol/d (714 mg/d). Supplementation had no effect on breast-milk calcium concentration or on maternal bone mineral content. Urinary calcium output was higher in supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(119 citation statements)
references
References 23 publications
4
111
1
1
Order By: Relevance
“…The decrease in urinary Ca output partly reflects the reduction in glomerular filtration rate after parturition (150) . Some studies, but not all (151) , have shown that urinary Ca output of BF mothers during the first 3 -6 months of lactation is lower than that of NBF mothers at the same stage postpartum or of NPNL women (91,115,152) .…”
Section: Intestinal Absorption and Renal Excretion Of Calciummentioning
confidence: 98%
See 1 more Smart Citation
“…The decrease in urinary Ca output partly reflects the reduction in glomerular filtration rate after parturition (150) . Some studies, but not all (151) , have shown that urinary Ca output of BF mothers during the first 3 -6 months of lactation is lower than that of NBF mothers at the same stage postpartum or of NPNL women (91,115,152) .…”
Section: Intestinal Absorption and Renal Excretion Of Calciummentioning
confidence: 98%
“…However, Ca supplementation studies of women during lactation (83,152) , and more recently during pregnancy (24) , have demonstrated that breast-milk Ca concentration is independent of maternal Ca intake, even amongst women with very low Ca intakes. In addition, because breast-milk Ca secretion is regulated by the casein, phosphate and citrate components, it is now recognised that maternal Ca intake is unlikely to influence breast-milk Ca secretion directly (173) .…”
Section: Influence On the Mother In Lactationmentioning
confidence: 99%
“…However, randomized trials and cohort studies have found that this increases urine calcium excretion without affecting milk calcium or the amount of bone resorbed during lactation (206,452,484,723,729,730) (see sects. IVE and VI).…”
Section: Human Datamentioning
confidence: 99%
“…Further information on this area of discussion is available (22)(23)(24)(25)(26)(27)(28)(29)(30)(31) .…”
Section: Stratum 5: Mineral Balancementioning
confidence: 99%